PERBANDINGAN HASIL BELAJAR MELALUI PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE DENGAN MODEL PEMBELAJARAN TEAMS GAMES TURNAMENT PADA TEMA PERISTIWA DALAM KEHIDUPAN DI KELAS V SD NEGERI NO. 064025 KECAMATAN MEDAN TUNTUNGAN TAHUN PEMBELAJARAN 2018/2019 - PURBA, HENY ROSA (Unversitas Katolik Santo Thomas, 2019)
This research aims to find out the comparison application of learning model Think Pair Sharewith Teams Games Turnamento study result of 5th grade students learning 1 and 5 of SD Negeri 064025, Medan Tuntungan subdistrict academic year 2018/2019 on. The types of research is experimental research with true experimental design method (Prates-Postes Control Group Design). The approach of research was quantitave. The population used in this study were 117 students of Elementary School 064025 in Medan Tuntungan Subdistrict. The research sample were the 60th students fifth grade A – B classes. The sampling technique in research is cluster sample. Data collection techniques using tests namely pre-test and post-test. Tests are used to obtain student learning outcomes data. The analysis techniq ue used is by using Microsoft Exel and Statistic Program For Social Science (SPSS) ver. 21.0. The result showed that there was comparised about result study from application Think Pair Share with Teams Games Turnamen model. The results of the calculation of data analysis showed that the increase in the average value of the pre-post test results in the experimental group I through the application of the Think Pair Share Model was 16.63.While the increase in the average value of the pre-post test results in the experimental group II amounted to 11.86. The difference in the average value of the experimental group II experimental group is only 4.77. Through the acquisition of tcount (4.224) > ttable (1,671), H0 is rejected. This proves that there was a comparison of learning outcomes through of Think Pair Share Model with Teams Games Turnamen model the application.